Enabling sustainable, productive smallholder farming systems through improved land and water management - CGIAR Research Program on Water, Land and Ecosystems (International Water Management Institute, 2017)
Farmer-led investments in agricultural land and water management (ALWM) are transforming livelihoods and food security across South Asia and sub-Saharan Africa. Potential exists for even greater benefits, for even more beneficiaries. Understanding what factors influence adoption and impact of ALWM interventions can help ensure sustainable, positive effects of future investments. WLE has designed a suite of tools and investment models to support policy makers and development agents to leverage and extend the investments farmers are already making.